Loss of a globally unique kelp forest from Oman - Coleman, M. A. (2022)
Kelp forests are declining in many regions globally with climatic perturbations causing shifts to alternate communities and significant ecological and economic loss. Range edge populations are often at most risk and are often only sustained through localised areas of upwelling or on deeper reefs. Here we document the loss of kelp forests (Ecklonia radiata) from the Sultanate of Oman, the only confirmed northern hemisphere population of this species. Contemporary surveys failed to find any kelp in its only known historical northern hemisphere location, Sadah on the Dhofar coast. Genetic analyses of historical herbarium specimens from Oman confirmed the species to be E. radiata and revealed the lost population contained a common CO1 haplotype found across South Africa, Australia and New Zealand suggesting it once established through rapid colonisation throughout its range. However, the Omani population also contained a haplotype that is found nowhere else in the extant southern hemisphere distribution of E. radiata. The loss of the Oman population could be due to significant increases in the Arabian Sea temperature over the past 40 years punctuated by suppression of coastal upwelling. Climate-mediated warming is threatening the persistence of temperate species and precipitating loss of unique genetic diversity at lower latitudes.